Enhanced identity privacy in UMTS. (2018) - Choudhury, Hiten; Roychoudhury, Basav; Saikia, Dilip Kr.
Subscriber's identity privacy in mobile networks has been an exciting research area. Earlier, researchers were focused on protecting it over the radio link between the mobile device and the serving network. Whereas now, they are considering the need for protecting the same from the serving network itself, due to the security and flexibility that it promises to bring into roaming situations. Towards this, numerous protocols have been proposed for mobile networks in general. However, in universal mobile telecommunications system (UMTS), one of the most widely deployed mobile networks, not much research has been conducted in this direction. In this paper, we make an effort to fill in this gap by proposing an extension that can be easily adapted in UMTS. We also establish the security, robustness and correctness of this extension through statistical, security and formal analysis.